Prevalencia de rinotraqueitis infecciosa bovina (IBR) en la Isla Santa Cruz - Zambrano Mendoza, Eitel Alejandro (2025)
Bovine infectious rhinotracheitis (IBR), caused by bovine herpesvirus type 1 (BoHV-1), is a major health concern in livestock. This study aimed to determine the serological prevalence of IBR in cattle from Santa Cruz Island, Galápagos. A total of 456 blood samples from 27 farms were analyzed using the IDEXX IBR gB X3 ELISA test. A general prevalence of 35.75% was obtained. Variables such as sex, geographical area, and herd size were evaluated. Although prevalence was higher in males (50%) than in females (35.41%), no statistically significant differences were found (p=0.1613). The geographical distribution showed significant differences (p=0.0007), with higher prevalence in Camote (43.05%) and Bellavista (50%). Herd size was not significantly associated (p=0.086). Surveys were applied to identify risk factors, revealing absence of vaccination, lack of quarantine measures, poor biosecurity, occasional animal introduction without diagnosis, and presence of wildlife and rodents. It was concluded that there is active virus circulation on the island and a fragile sanitary situation, highlighting the need to implement epidemiological control strategies tailored to the insular context, emphasizing health education, epidemiological surveillance, and improved sanitary management.